Fen Bilgisi Öğretmen Adaylarının Gün Uzunluğunun Değişimine İlişkin Zihinsel Modelleri - Bolat, Mualla; Türk, Cumhur; Ocak İskeleli, Nazan (Muş Alparslan Üniversitesi, 2018)
This present study purposed to reveal the mentalmodels of science preservice teachers on the reason for the change in daylength that is related to many disciplines. The study was conducted with 286preservice teachers studying (at grades from 1st to 4th)in the department of science teaching of a university located in Black SeaRegion in Turkey during 2017-2018 academic year. An open-ended question wasasked to the preservice teachers. These answers were evaluated according to thedescriptive analysis and were examined in 3 different models. It was alsoobserved that the number of preservice teachers with a primitive model was thehighest in the first grade, and that the number of preservice teachers with a synthesismodel and a scientific model increased as the grade of education progressed. Onthe basis of the results of the study, it was recommended that it would bebeneficial to create the teaching activities that will enable the preserviceteachers to comprehend the shape and movements of the Earth and the eventscaused by their interaction with the Sun conceptually rather than memorization.

Buçalışmada pek çok bilim dalı ile ilişkisi olan gün uzunluğunun değişiminedeniyle ilgili fen bilgisi öğretmen adaylarının zihinsel modellerini ortayaçıkarmak amaçlanmıştır. Çalışma 2017-2018 eğitim-öğretim yılında Türkiye’ninKaradeniz Bölgesi’ndeki bir üniversitenin fen bilgisi öğretmenliği bölümünde öğrenimgörmekte olan (1, 2, 3 ve 4. sınıf) 286 öğretmen adayı ile gerçekleştirilmiştir.Öğretmen adaylarına açık uçlu bir soru yöneltilmiştir. Cevaplar betimselanalize göre değerlendirilerek, 3 farklı modelde incelenmiştir. İlkel modelesahip öğretmen adayının en fazla birinci sınıfta olduğu, sınıf düzeyi artıkçasentez model ve bilimsel modele sahip öğretmen adayı sayısının arttığıgörülmüştür. Çalışma sonuçlarından yola çıkarak Dünya’nın şekli, hareketleri vebunların Güneşle olan etkileşiminin sebep olduğu olayların öğretmen adaylarınaezbere bilgi yerine kavramsal olarak anlamasını sağlayacak öğretimetkinliklerinin yapılmasının yararlı olacağı önerilmiştir.
Mental Models of Preservice Science Teachers on the Change in Day Length
anemon
Keywords: Day Length; Mental Model; Science; Preservice Teacher; Gün Uzunluğu; Zihinsel Model; Fen Bilgisi; Öğretmen Adayı